2020
DOI: 10.3390/pathogens9050335
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping, Assessment of Virulence and Antibacterial Resistance of the Rostov Strain of Mycobacterium tuberculosis Attributed to the Central Asia Outbreak Clade

Abstract: The Central Asia Outbreak (CAO) clade is a growing public health problem for Central Asian countries. Members of the clade belong to the narrow branch of the Mycobacterium tuberculosis Beijing genotype and are characterized by multidrug resistance and increased transmissibility. The Rostov strain of M. tuberculosis isolated in Russia and attributed to the CAO clade based on PCR-assay and whole genome sequencing and the laboratory strain H37Rv were selected to evaluate the virulence on C57Bl/6 mice models by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…In the first study, CAO was among the least lethal strains with 90% survived animals after 125 days [ 14 ]. This is drastically different from the second study [ 22 ] where all CAO-infected mice succumbed within 47 days. This could be due to different study design and used animals, although could be partly explained by that fact that CAO strains originated from different parts of Russia (St. Petersburg in North and Rostov in South).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In the first study, CAO was among the least lethal strains with 90% survived animals after 125 days [ 14 ]. This is drastically different from the second study [ 22 ] where all CAO-infected mice succumbed within 47 days. This could be due to different study design and used animals, although could be partly explained by that fact that CAO strains originated from different parts of Russia (St. Petersburg in North and Rostov in South).…”
Section: Discussioncontrasting
confidence: 92%
“…The importance of using comparable models of virulence is exemplified by studies of the other important Beijing subtype, the CAO strain [ 14 , 22 ]. CAO stands for Central Asian Outbreak that is a particular cluster within a larger and more heterogeneous Central Asian/Russian clade of the Beijing genotype modern sublineage (Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…The virulent laboratory strain M. tuberculosis H37Rv was obtained from the SCPM–Obolensk (ID B-4825). Mycobacterial cells were grown in Middlebrook 7H9 broth with OADC supplement (BD, Franklin Lakes, NJ, USA) containing 0.05% Tween 80 at 37 °C under static conditions (for in vivo experiments) or with agitation (for in vitro studies) and stored in frozen stocks at minus 70 °C as described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that a strain of the CAO sublineage showed the same level of virulence for C57BL/6 mice as reference strain H37Rv [ 20 ]. In contrast, we recently characterized the strain Rostov, which was significantly more virulent for C57BL/6 mice than the strain H37Rv, as belonging to the CAO sublineage [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The work of Mupfumi L. et al investigates the dynamics of the host immune response during MTB infection in HIV/TB co-infected patients, defining the functional, activation, and differentiation profile of MTB-specific T-cells during antiretroviral treatment [5]. The research article by Fursov et al [6] investigates the genetic and phenotypic profile of the MTB strain Rostov, belonging to the Central Asia Outbreak Clade (CAO) of the Beijing genotype. This strain has been attributed to the pre-extensively drug-resistant (XDR) tuberculosis group.…”
Section: Editorialmentioning
confidence: 99%